Social-Cultural Ecosystem Services of Sea Trout Recreational Fishing in Norway - Liu, Yajie; Bailey, Jennifer L.; Davidsen, Jan G. (Frontiers in Marine Science, 2019)
ABSTRACT This paper explores the ecosystem services provided by anadromous brown trout (often termed sea trout) populations in Norway. Sea trout is an important species in both freshwater and marine ecosystems and provides important demand-driven ecological provisioning and socio-cultural services. While the sea trout once provided an important provisioning service through a professional fishery and subsistence fishing, fishing for sea trout in the near shore coastal areas and in rivers is today a very popular and accessible recreational activity and generates primarily socio-cultural services. The recreational fishery contributes to local cultural heritage, its folkways and lore, to the development and transfer of local ecological knowledge and fishing experience to the young and to human well-being. As a salmonid species, the sea trout is sensitive to negative environmental conditions in both freshwater and marine coastal areas and is in general decline. A recent decision to expand production of farmed salmon may increase pressure on stocks. Good management of recreational fishing is accordingly important for the species to thrive, but knowledge of what fishers shall value with respect to fishing sea trout and what management measures they will accept is limited. Researchers sought to capture information about non-extractive direct use value (non-monetary) of the sea trout recreational fishery using questionnaire surveys targeting Norwegian anglers around the country. Results indicate that the most important ecosystem services delivered by recreational sea trout fisheries are social-cultural ecosystem services at the level of individual fishers; fishing sea trout most likely also has important social functions. Fishers are prepared to accept stricter management measures that reduce catches and allow fishing to continue but they oppose paying higher fees.